A Recurrence Relation Related to the Reve’s Puzzle: Reve’s Puzzle Related Recurrence - Majumdar, Abdullah-Al-Kafi (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In a recent paper, Majumdar [1] studied, to some extent, the generalized recurrence relation, introduced by Matsuura [2] : ( )  ( ) 2 1 1 s MT n, min MT n s, , s n          where n ≥ 1 and  ≥ 2 are integers. It may be mentioned here that,  = 2 corresponds to the Reve’s puzzle, introduced by Dudeney [3]. In this paper, we study more closely the properties of the function MT(n,  ), and give a closed-form expression of it when  = 2i (for any integer i ≥ 2).